Characterization of microcrystalline cellulose derived from saccharum officinarum L. (Sugarcane) Bagasse - Cativo, Ashley Nichole M.; Prudente, Bleszie Grace D.
The increasing global demand for microcrystalline cellulose (MCC) has driven the search for sustainable and low-cost alternatives, and sugarcane bagasse has been of interest due to its high cellulose content. This study aimed to characterize MCC derived from the bagasse of S. officinarum var. PSR 2001-105 cultivated in Mapalacsiao, Tarlac City, Philippines. It also aimed to evaluate the physicochemical properties of MCC derived from S. officinarum bagasse through pharmacopeial and non-pharmacopeial tests. An alkali and acid pretreatment method using sodium hydroxide (NaOH) and sulfuric acid (H2SO4 ) was performed on the bagasse powder to extract the cellulose. This was followed by acid hydrolysis using hydrogen chloride (HCl) to convert the cellulose into bagasse MCC (BMCC). A yield of 0.1838g BMCC/g of sugarcane bagasse was obtained from the extraction method. Characterization of the bagasse BMCC was conducted using select pharmacopeial and non-pharmacopeial tests. BMCC yielded similar results to previous studies in terms of FTIR and SEM results, but indicate the need for further delignification and hydrolysis, respectively. Further optimization of the extraction process to improve percent yield and purity of BMCC, and addition of in-process identification tests to ensure complete conversion of cellulose to MCC is recommended.